Flavonoids Alleviate Peripheral Neuropathy Induced by Anticancer Drugs - Manaal Siddiqui (18891637) (2021)
Purpose: This study aimed to assess the potential of flavonoids in combating CIPN. Methods: PubMed and Google Scholar were used, and studies that investigated flavonoids in models of CIPN and models of neuropathic pain similar to CIPN were included. Only studies investigating peripheral mechanisms of CIPN were used. Results: Flavonoids inhibit several essential mechanisms of CIPN, such as proinflammatory cytokine release, astrocyte and microglial activation, oxidative stress, neuronal damage and apoptosis, mitochondrial damage, ectopic discharge, and ion channel activation. They decreased the severity of certain CIPN symptoms, such as thermal hyperalgesia and mechanical, tactile, and cold allodynia. Conclusions: Flavonoids hold immense promise in treating CIPN; thus, future research should investigate their effects in humans. Specifically, precise pharmacological mechanisms and side effects need to be elucidated in human models before clinical benefits can be achieved. Other Information Published in: Cancers License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.3390/cancers13071576